EFFECTIVENESS OF CHERRY LEAF EXTRACT (Muntingia calabura) WITH DIFFERENT LEVELS AS TREATMENT OF SEEDS OF SANGKURIANG CATFISH (Clarias gariepinus) INFECTED BY Trichodina sp - Moh. Nurhuda; Marry Ann Kholista; Yuliani Ismi; Nurfitri Maulidiya; Hariyadi Hariyadi; Riza Rahman Hakim (IJOTA (Indonesian Journal of Tropical Aquatic), 2018)
Sangkuriang catfish (Clarias gariepinus) is a leading commodity of Indonesian freshwater fishery. Production continues to increase in 2016 reached 22%. cultivators experience constraints on seeding and enlargement due to ectoparasites Trichodina sp. this parasite attacks the outer part of the body marked by the spots on the body. Prevention and treatment of many usses of chemicals that can adversely affect the human body and environtment, so it takes another alternative to replace these chemicals that can adversely affect the human body and environment, so it takes another alternative to replace these chemicals. Cherry Leaf contain compounds Flavonoid, Tannin, Triterpenoid, Saponin and Polifenol as antioxidants, Cherry Leaf useful as an antibacterial. The method used in this research is the experimental method and using Completely Randomized Design (RAL). Concentrations of cherry leaf extract (Muntingia calabura) given include 1%, 2%, 3%, 4% and 5% there were 5 treatments and 4 replications. The data obtained were analyzed by ANAVA method (variance analysis) followed by LSD test. The results showed that the use of cherry leaf extract (Muntingia calabura) in treating Trichodina sp parasite has a very real effect with the best value on the presentation of Leukocrit is 2% concentration that produces Leukocrit percentage of 2.68% and percentage of Hematocrit 2% with Hematocrit yield of 11.83%. The clinical symptoms are white spots in all body, pale color, decreased appetite of the mucus that comes out, often rubbing the body to the wall. The result of water quality measurement shows temperature: 24 - 27,2oC, DO: 4,1 - 6,9 and pH: 6 - 8.KEY WORDS: Muntingia calabura, Trichodiniasis, Sangkuriang Catfish, Leukocrit, Hematocrit.